Comparison of anti-plaque and anti-gingivitis effect of curcumin and chlorhexidine mouth rinse in the treatment of gingivitis: A clinical and biochemical study - Lalitha Tanjore Arunachalam; Uma Sudhakar; Johney Vasanth; Sophia Khumukchum; Varsha Vardhini Selvam (Wolters Kluwer Medknow Publications, 2017)
Background: To evaluate and compare the effect of curcumin (CMN) mouth rinse with chlorhexidine (CHX) mouth rinse on clinical parameters and reactive oxygen metabolites (ROM) levels in participants with chronic gingivitis. Materials and Methods: Thirty plaque-induced generalized chronic gingivitis participants were randomly assigned to three groups - Group I (control/saline), Group II (CHX), and Group III (CMN), respectively. Baseline plaque index (PI), gingival index (GI), and salivary ROM were estimated, and oral prophylaxis was done. The parameters were recorded and evaluated again at the end of 4 weeks. Results: Overall, the three groups have shown a significant reduction in PI, GI, and ROM levels at the end of 4 weeks. However, on intragroup comparison, only CMN group have shown significant reduction in ROM levels at the end of 4 weeks (P < 0.05). Conclusion: CMN mouth rinse can be considered as an alternative antigingivitis agent to CHX because of its anti-inflammatory and antioxidant properties.